Self-supporting three-dimensional ZnIn2S4/PVDF–poly(MMA-co-MAA) composite mats with hierarchical nanostructures for high photocatalytic activity - Peng, Shengjie (2013)
This paper reports the fabrication of self-supporting three-dimensional ZnIn2S4/PVDF–poly(MMA-co-MAA) (ZIS/Polymer) composite mats with hierarchical nanostructures by a simple combination of an electrospinning technique and a hydrothermal process and their high photocatalytic activity. The characterization results show that ZnIn2S4 (ZIS) nanosheets with a thickness of about 20 nm distribute uniformly on the surface of the nanofiber polymers to form mats. The coverage density of the ZIS nanosheet coating on the surface of the polymer mats could be controlled by simply adjusting the amount ratios of feeding reactants to polymers. Furthermore, the growth process of ZIS coating is investigated based on time-dependent experiments. The obtained ZIS/Polymer heteroarchitectures show high photocatalytic property and stability to degrade methyl orange (MO) because of the formation of hierarchical nanostructures, which might improve the adsorption and catalysis of the dyes. Due to the self-supporting property of the mats, the ZIS/Polymer mats could be laid or hung conveniently anywhere under solar irradiation and recycled easily, which provides a solution to the separation problem for conventional catalysts that are small in size. The study may open a new way to build hierarchical device fabrics with optical and catalytic properties.